2021
DOI: 10.3389/fneur.2021.699838
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular MRI Compared to Echocardiography to Identify Cardioaortic Sources of Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: To compare the diagnostic yield of echocardiography and cardiovascular MRI (CMR) to detect structural sources of embolism, in patients with ischemic stroke with a secondary analysis of non-stroke populations.Methods and Results: We searched MEDLINE/Embase (from 01.01.2000 to 24.04.2021) for studies including CMR to assess prespecified sources of embolism. Comparison included transthoracic and/or transesophageal echocardiography. Two authors independently screened studies, extracted data and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…In a recent meta-analysis including 5 studies and 236 patients, CMRI showed a 29.3% (95% CI, 23.6%–35.0%) detection yield compared with 53.7% (95% CI, 47.4%–59.9%) for TEE ( P <0.001). 26 Despite its relatively low diagnostic yield for PFO, CMRI may still be useful for understanding the role of right atrial flow patterns on the risk of paradoxical embolism. However, its current use remains investigational.…”
Section: Recent Developments and Unknowns In Pfo Diagnosismentioning
confidence: 99%
“…In a recent meta-analysis including 5 studies and 236 patients, CMRI showed a 29.3% (95% CI, 23.6%–35.0%) detection yield compared with 53.7% (95% CI, 47.4%–59.9%) for TEE ( P <0.001). 26 Despite its relatively low diagnostic yield for PFO, CMRI may still be useful for understanding the role of right atrial flow patterns on the risk of paradoxical embolism. However, its current use remains investigational.…”
Section: Recent Developments and Unknowns In Pfo Diagnosismentioning
confidence: 99%
“…When comparing the two, cardiac CT and CMR have comparable diagnostic performance in visualising LA appendage thrombus and high-grade valve disease/calcifications, with both being inferior to TOE in imaging valvular AF, mitral valve prolapse, and highgrade valve disease/calcifications [62]. Cardiac CT is superior to CMR in terms of imaging aortic dissection, aortic aneurysm, and complex aortic plaques [62].…”
Section: Cardiac Computed Tomography (Ct) and Cardiac Magnetic Resona...mentioning
confidence: 99%
“…7 However, CMR is not a part of the routine diagnostic work-up in AIS patients and its availability is limited. 4,8 Moreover, data concerning the diagnostic value of CMR in patients with elevated cardiac biomarkers in the context of AIS is very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…3 Different cardiac pathologies may be identified by performing cardiac magnetic resonance imaging (CMR). 4 CMR is recommended for the evaluation of a variety of cardiac conditions including cardiomyopathies, myocarditis, cardiac masses, cardiac thrombi, or pericardial diseases. 5 In addition, by examining the presence and pattern of late-gadolinium enhancement (LGE), one can distinguish lesions consistent with (chronic) myocardial infarction from nonischemic lesions.…”
Section: Introductionmentioning
confidence: 99%